Konsep Kekuasaan Michel Faucault - Abdullah Khozin Afandi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2012)
This article attempts to outline the concept of Michel Foucault's power based on the major works that he wrote during his lifetime. Foucault asserts that power exists everywhere, especially concerning the relationship between power and the discourse of knowledge. Here, for him, the will to truth is the expression of the will to power. It is impossible for the knowledge to be neutral and pure. Therefore, there will always be a correlation between the two matters, i.e., the knowledge contains power, just like the power contains knowledge. This means that power is one dimension of the relation. Where there is a relationship, there is power.